Analysis of Self-Oscillations in Three-Level Hysteresis Current Controlled H-Bridge. Issue 2 (2020) - Krämer, Andreas; Bohn, Christian; Ali, Abid
Abstract: In direct-current control scheme, self-oscillations or limit cycles occur due to the hysteresis controller. In this contribution, the different types of self-oscillations in a three-level hysteresis current controlled H-bridge are analyzed. The investigations are based on Tsypkin's method for self-oscillations in relay control systems. So, the conditions for the different types of self-oscillations are given and the frequency of the oscillation and the on-to-off-ratio or pulse width of the switching hysteresis output are calculated exactly. The values correspond to the switching frequency and the duty cycle of the H-bridge. Furthermore, some analyses about the transfer characteristic of the control loop are made.